K filozofiii sociálnych vied - Sedová, Tatiana (Organon F, 2000)
The paper examines questions which are connected with some philosophical issues of social science. Are social structures better conceived of as systems of law and forces, or as webs of practices and meanings? Can action be better viewed as rational behaviour, or as self-expression? What is a social fact, and how one is differed from a natural, brute fact? By exploring such questions, one can reflect upon the nature of scientific method in social science. The aim of the article is to show, which central problems make up the philosophy of social science.